Raising Teachers’ Awareness of the Significance of Formulaic Sequences in Writing Proficiency - Khoualdi, Safa (Journal of Human Sciences, 2017)
In recent years, the academic arena witnessed a renewed interest in the role of vocabulary and with it the phenomenon of formulaic sequences (these are multi-word units which are stored and retrieved as whole from memory) came to the fore. Much research proved that these sequences are closely related to writing proficiency. In fact, several studies were carried out to investigate the use of formulaic sequences by language learners; however, investigating these sequences from the perspective of teachers was largely unexplored. Therefore, the present study attempted to explore English as a foreign Language (EFL) teachers’ awareness of the formulaicity of language, their attitudes as well as practices regarding the incorporation of these sequences in writing classrooms. To achieve this purpose, a questionnaire was administered to 12 teachers of Written Expression at the department of English at Larbi Ben M’hidi University of Oum El Bouaghi. The obtained results showed the teachers’ lack of awareness of the formulaicity of language. The study also revealed that though the teachers found formulaic sequences of high importance in improving writing proficiency and showed positive attitudes towards their inclusion in their writing classrooms, the instruction of these sequences was not really part of their teaching agenda.